Answer:
Step-by-step explanation:
The given equations are:
(1)
and
(2)
Now, simply adding equation (1) and equation (2), we get
![2x+3y+x-3y=15+3](https://tex.z-dn.net/?f=2x%2B3y%2Bx-3y%3D15%2B3)
![3x=18](https://tex.z-dn.net/?f=3x%3D18)
![x=6](https://tex.z-dn.net/?f=x%3D6)
Now, substituting the value of x=6 in equation (2). we get
![6-3y=3](https://tex.z-dn.net/?f=6-3y%3D3)
![6-3=3y](https://tex.z-dn.net/?f=6-3%3D3y)
![3=3y](https://tex.z-dn.net/?f=3%3D3y)
![y=1](https://tex.z-dn.net/?f=y%3D1)
Thus, the values of x and y are 6 and 1 respectively.
In order to solve the system of solution, beau can see that in both the given equations, coefficient of y is same and is with opposite sign, thus simply adding both the equations will eliminate y and she will get the value of x and then substituting the value of x in any of the equations, she can get the value of y. With this, she can get closer to the solution.
Answer:
27
Step-by-step explanation:
the sequence is 4 added to each number. 4 added to 23 is 27
7 / 7 = 1
3 + 1 = 4
4 + 3 and 1 / 3 = 7 and 1 / 3
Answer:
63
Step-by-step explanation:
hhehehehhehehehehh hope this helps
4^4 + 1/2
= (4×4×4×4) + 1/2
= 256 + 1/2
= 256 + 0.5
= 256.5